Machine Learning-Augmented Propensity Score Analysis of Percutaneous Coronary Intervention in Over 30 Million Cancer and Non-cancer Patients - Monlezun, Dominique J.; Lawless, Sean; Palaskas, Nicolas; Peerbhai, Shareez; Charitakis, Konstantinos; Marmagkiolis, Konstantinos; Lopez-Mattei, Juan; Mamas, Mamas; Iliescu, Cezar (Frontiers in Cardiovascular Medicine, 2021)
Background: It is unknown to what extent the clinical benefits of PCI outweigh the risks and costs in patients with versus without cancer and within each cancer type. We performed the first known nationally representative propensity score analysis of PCI mortality and cost among all eligible adult inpatients by cancer and its types. Methods: This multicenter case-control study used machine learning–augmented propensity score–adjusted multivariable regression to assess the above outcomes and disparities using the 2016 nationally representative National Inpatient Sample. Results: Of the 30,195,722 hospitalized patients, 15.43% had a malignancy, 3.84% underwent an inpatient PCI (of whom 11.07% had cancer and 0.07% had metastases), and 2.19% died inpatient. In fully adjusted analyses, PCI versus medical management significantly reduced mortality for patients overall (among all adult inpatients regardless of cancer status) and specifically for cancer patients (OR 0.82, 95% CI 0.75-0.89; p<0.001), mainly driven by active versus prior malignancy, head and neck and hematological malignancies. PCI also significantly reduced cancer patients’ total hospitalization costs (beta USD -8,668.94, 95% CI -9,553.59- -7,784.28; p< 0.001) independent of length of stay. There were no significant income or disparities among PCI subjects. Conclusions: Our study suggests among all eligible adult inpatients, PCI does not increase mortality or cost for cancer patients, while there may be particular benefit by cancer type. The presence or history of cancer should not preclude these patients from indicated cardiovascular care.